Picture-Based Recognition of Smokers: a Novel Visual Method - Marja-Leena Kauronen; Olli Lehtonen; Kirsi Purhonen; Valdemar Kallunki; Angelika Polak (Ekonometria)
It is important to obtain a deeper understanding of the social context of smoking, which may support finding new ways to hinder the development of a smoker's identity. The authors developed the Picture Based Recognition of Smokers (PBRS) method in order to understand the identity markers of the social and visual contexts related to adolescent smoking. The differences in identifying non- -smokers and smokers between traditional text-based questionnaires and PBRS were compared in a discriminatory analysis conducted by comparison clouds and correlograms. The ability of these methods to predict adolescent smokers was tested with a regression model combined with permutation analysis. The result of word clouds confirmed that interpretations of the visual identity markers of pictures differ between non-smokers and smokers. PBRS had a better success rate of predictions than the text-based questionnaires. This approach develops preventive interventions which do not stigmatize the intervention group.(original abstract)